2022
DOI: 10.3390/ijerph192013147
|View full text |Cite
|
Sign up to set email alerts
|

Social Capital, Political Efficacy and Chinese Residents’ Willingness to Participate in Food Safety Governance

Abstract: Residents play an important role as one of the main actors in food safety governance. To build a pattern of food safety risk co-governance, the positive and effective participation of residents is vital. This study first establishes a comprehensive analysis framework combining social capital theory and political efficacy theory. Data from a survey of 714 residents in Shandong Province, China, were analysed through structural equation modelling and fuzzy-set qualitative comparative analysis (fsQCA) to examine t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 47 publications
1
3
0
1
Order By: Relevance
“…There is no doubt that these actions have deepened people's trust in the government and recognition of its regulatory capabilities. This finding is consistent with the findings of Du et al, who concluded that institutional trust could have a positive influence on individuals' willingness to report [17]. In the case of take-home platforms, individuals' willingness to blow the whistle has not been influenced by their perceived efficacy of the private governance system.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…There is no doubt that these actions have deepened people's trust in the government and recognition of its regulatory capabilities. This finding is consistent with the findings of Du et al, who concluded that institutional trust could have a positive influence on individuals' willingness to report [17]. In the case of take-home platforms, individuals' willingness to blow the whistle has not been influenced by their perceived efficacy of the private governance system.…”
Section: Discussionsupporting
confidence: 91%
“…The concept of "social governance" was not introduced in China until 2013 and has not been around long enough for public involvement in food security governance to be explored. Much of the research on collaborative public-private governance has focused on summaries of overseas experiences and the willingness of residents to participate and third-party interventions [17,18], with the belief that residents play an important role as one of the key participants in food safety governance [19], but there has been little research on the factors influencing whistleblowing on Food Violations.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, previous studies have indicated that individuals with higher levels of social capital are more likely to have the resources, connections, and information necessary to engage in political activities, which can increase their political selfefficacy (Browning et al, 2004;Anderson, 2010). Moreover, social capital may indirectly boost political self-efficacy by providing individuals with a sense of empowerment and support, allowing them to feel more capable and confident in their political participation (Levy, 2013(Levy, , 2018Quintelier, 2015;Du et al, 2022). Social capital may also expose individuals to diverse political perspectives and ideas, which can broaden their political knowledge and competencies, further increasing their self-efficacy in the political sphere.…”
Section: Social Capital and Political Self-e Cacymentioning
confidence: 99%
“…Even though the components of social capital have been measured separately, they are still usually expected to function in the same way, that is, to increase political self-efficacy (Du et al, 2022). However, during recent years, scholars have still increasingly approached the concept of social capital more critically by aiming to create a converging theory, which could comprehensively bring together all of its dimensions (e.g., Claridge, 2018;Gelderblom, 2018).…”
Section: Social Capital and Political Self-e Cacymentioning
confidence: 99%
“…Lebih lanjut Nie & Tang (2022) menjelaskan kawasan lindung yang dibuka menjadi kawasan pariwisata membutuhkan kolaborasi antar stakeholder untuk menjaga kawasan lindung itu sendiri dan menjadikannya kawasan pariwisata berkelanjutan. Si et al (2022) dan Du et al (2022) menjabarkan pariwisata berkelanjutan lebih berfokus pada kebiasaan masyarakat lokal dalam menjaga pariwisatanya.…”
Section: A Pendahuluanunclassified